E-government: el voto electrónico sobre Internet - Pesado, Patricia Mabel (2008)
This paper presents a first experience in E-Voting over Internet, integrating students from different regional centers of the School of Computer Science at National University of La Plata. System hardware architecture and some important software aspects are discussed compared with previous R&D work of the same group. Finally the main related research lines are presented, focusing on the use of technology in E-Government applications.